Acute norepinephrine reuptake inhibition decreases performance in normal and high ambient temperature - Roelands, Bart; Goekint, Maaike; Heyman, Elsa; Piacentini, Maria Francesca; Watson, Philip; Hasegawa, Hiroshi; Buyse, Luk; Pauwels, Frank; De Schutter, Guy; Meeusen, Romain (Journal of applied physiology (1985), 2008)
Combined inhibition of dopamine (DA)/norepinephrine (NE) reuptake improves exercise performance and increases core temperature in the heat. A recent study demonstrated that this effect may primarily be related to increased DA activity. NE reuptake inhibition (NERI), however, has received little attention in humans, certainly in the heat, where central fatigue appears to be a main factor influencing performance. Therefore the present study examines the effect of NERI (reboxetine) on exercise capacity, thermoregulation, and hormonal response in normal and high temperature. Nine healthy well-trained male cyclists participated in this study. Subjects ingested either placebo (Pla; 2 x 8 mg) or reboxetine (Rebox; 2 x 8 mg). Subjects exercised in temperate (18 degrees C) or warm (30 degrees C) conditions and cycled for 60 min at 55% W(max) immediately followed by a time trial (TT; Pla18/Rebox18; Pla30/Rebox30) to measure exercise performance. Acute NERI decreased power output and consequently exercise performance in temperate (P = 0.018) and warm (P = 0.007) conditions. Resting heart rate was significantly elevated by NERI (18 degrees C: P = 0.02; 30 degrees C: P = 0.018). In Rebox18, heart rate was significantly higher than in the Pla18, while in the heat no effect of the drug treatment was reported during exercise. In Rebox30, all hormone concentrations increased during exercise, except for growth hormone (GH), which was significantly lower during exercise. In Rebox18, prolactin (PRL) concentrations were significantly elevated; GH was significantly higher at rest, but significantly lower during exercise. In conclusion, manipulation of the NE system decreases performance and modifies hormone concentrations, thereby indicating a central NE effect of the drug. These findings confirm results from previous studies that predominantly increased DA activity is important in improving performance.